Diagnostic Accuracy of the 2002 EULAR Criteria for the Clinical Suspicion of Rheumatoid Arthritis and the Sensitivity of the New 2010 ACR/EULAR Classification Criteria in “Early Arthritis” - Lyudmila SIZOVA, (Archives of Rheumatology, 2011)
Objectives: In this study we investigated the diagnostic and prognostic significance of the 2002 European League Against Rheumatism (EULAR) criteria for the clinical suspicion of rheumatoid arthritis (RA) and the sensitivity of the new 2010 American College of Rheumatology (ACR)/EULAR classification criteria for RA in patients with “early arthritis”. Patients and methods: The subjects were 250 outpatients (211 females, 39 males; mean age 46.1±11.8 years; range 19 to 73 years) with ”early arthritis”. The mean disease duration was 4.9±3.3 months. The criteria of inclusion of patients in the study were: (i) patients aged 18 years and older, (ii) clinical suspicion of RA according to EULAR (2002) criteria or persistent arthritis/arthralgia (>6 weeks), (iii) duration of disease <1 year, and (iv) written consent of the patient to participate in the study. The exclusion criteria were: (i) presence of a definite diagnosis of other rheumatic diseases before the onset of the study, and (ii) refusal of the patient to participate in the study. The diagnostic significance of the criteria was determined by the sensitivity and specificity. Predictive significance was estimated on positive and negative predictive values. The diagnostic effectiveness was also considered. Results: The 2002 EULAR criteria had higher diagnostic accuracy in identifying all three criteria in the patients. The negative predictive values ranging from 87.84% to 98.0% indicate that the absence of one of these criteria, especially arthritis of three or more joints, reduces the probability of RA diagnosis and requires investigation for other possible diseases with involvement of the joints. Two criteria was found to have the highest sensitivity among the 2010 ACR/EULAR classification criteria for RA: (i) the presence of synovitis in at least one joint, and (ii) symptom duration ≥6 weeks. ”Definite” RA could be identified in 98 (86%) patients according to new criteria (a score of ≥6/10) at the beginning of the study. Conclusion: The obtained data indicates the feasibility of using the 2002 EULAR criteria for screening patients with early RA and the usefulness of the new 2010 ACR/EULAR classification criteria for identification patients with ”definite RA” and initiation of therapy with disease-modifying antirheumatic drugs.